Bioactive Substances and Skin Health: An Integrative Review from a Pharmacy and Nutrition Perspective - Rafael Jesús Giménez Martínez; Francisco Rivas García; Joan Carles March Cerdá; Ángela Hernández-Ruíz; Martha Irene González Castro; María-Isabel Valverde-Merino; Felipe José Huertas Camarasa; Fuensanta Lloris Meseguer; Margarita López-Viota Gallardo (Pharmaceuticals)
The skin is one of the largest and most important organs of our body. There are numerous factors that are related to skin health, including lifestyle factors, nutrition, or skin care. Bioactive substances from plant and marine extracts play a key role in skin health. The aim of this research was to compile the main evidence on skin and bioactive substances. An integrative review was performed, reporting the main findings according to PRISMA (2020). Thirteen search equations were developed. After the applications of the equations and the process of screening and selection of articles, 95 references were compiled. The main results related to bioactive compounds were classified into food-derived components, nutraceuticals, symbiotics, active substances of marine origin, and substances from plant extracts). There are several factors that indicate that the use of bioactive compounds are interesting for skin health, highlighting some dietary nutrients, substances obtained from plant extracts and metabolites of marine origin that, showing anti-inflammatory and antimicrobial effects, are related to the improvement of some skin conditions or are active principles for cosmetics.